Pengaruh Model Pembelajaran Problem Based Learning Berbantuan Quizizz Terhadap Hasil Belajar Peserta Didik Pada Mata Pelajaran Ekonomi Di SMAN 8 Tasikmalaya - Sari, Ira Nurmala; Aisyah, Iis; Gumilar, Gugum (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
The research was motivated by the low learning outcomes of students in economics subjects in class X SMAN 8 Tasikmalaya. The purpose of the study was to determine the effect of the Problem Based Learning learning model assisted by Quizizz on student learning outcomes. This study uses the Quasi Experiment method with a quantitative approach. The population in this study were class X students of SMAN 8 Tasikmalaya as many as 252 students. The sampling technique in the study used purposive sampling technique, namely 72 students with an experimental class of 36 students using the Problem Based Learning learning model assisted by Quizizz and 36 students in the control class using a conventional learning model. The results showed that there were differences in the improvement of student learning outcomes in experimental classes using the Problem Based Learning learning model assisted by Quizizz and control classes using conventional learning models on student learning outcomes in measurements at the beginning and at the end of learning in economic subjects, thus it can be concluded that the Problem Based Learning learning model assisted by Quizizz has an effect on improving student learning outcomes.